Mechanical knowledge does matter to tool use even when assessed with a non‐production task: Evidence from left brain‐damaged patients. Issue 2 (20th December 2017) - Lesourd, Mathieu; Budriesi, Carla; Osiurak, François; Nichelli, Paolo F.; Bartolo, Angela
Abstract : In the literature on apraxia of tool use, it is now accepted that using familiar tools requires semantic and mechanical knowledge. However, mechanical knowledge is nearly always assessed with production tasks, so one may assume that mechanical knowledge and familiar tool use are associated only because of their common motor mechanisms. This notion may be challenged by demonstrating that familiar tool use depends on an alternative tool selection task assessing mechanical knowledge, where alternative uses of tools are assumed according to their physical properties but where actual use of tools is not needed. We tested 21 left brain‐damaged patients and 21 matched controls with familiar tool use tasks (pantomime and single tool use), semantic tasks and an alternative tool selection task. The alternative tool selection task accounted for a large amount of variance in the single tool use task and was the best predictor among all the semantic tasks. Concerning the pantomime of tool use task, group and individual results suggested that the integrity of the semantic system and preserved mechanical knowledge are neither necessary nor sufficient to produce pantomimes. These results corroborate the idea that mechanical knowledge is essential when we use tools, even when tasks assessing mechanical knowledge do not require the production of any motor action. Our results also confirm the value of pantomime of tool use, which can be considered as a complex activity involving several cognitive abilities (e.g., communicative skills) rather than the activation of gesture engrams.